DISTRIBUTION ANALYSIS OF DOCTORS IN INDONESIA - Agung Dwi Laksono; Ilham Akhsanu Ridlo; Ernawaty Ernawaty (Universitas Airlangga, 2020)
Background: The distribution of health workers in Indonesia raises an interesting discussion since Indonesia as an archipelagic country has a wide geography and challenges for fulfilling equitable health services.Aim: This study identified factors related to the distribution of doctors in provinces of Indonesia.Methods: Advanced analysis of secondary data was done and obtained from the